Application of Spectroscopy Methods for Indication and Identification of Pathogenic Biological Agents - D. V. Utkin; V. E. Kouklev; P. S. Erokhin; N. A. Ossina (Проблемы особо опасных инфекций, 2011)
The review presents data on application of UV, IR and optical spectroscopy methods for non-specific indication of pathogenic biological agents, and IR Fourier spectroscopy, and Raman spectroscopy - for their identification. Considered are advantages, disadvantages and prospects of different spectroscopy methods application for monitoring of the environment for the presence of pathogenic biological agents.